Strategic planning for information systems - Ward, John; Peppard, Joe. (Chichester, West Sussex, England ; New York : J. Wiley, 2002)
This book demonstrates why strategic planning for information systems is essential to organisational success, especially in times of increasingly rapid change.
Includes bibliographical references and index.
osa16/05/13
Loan
Keywords: Management information systems; Strategic planning; Business; Business